Praktyka wdrażania CSR w polskich przedsiębiorstwach w opinii doradców - Rogowski, Robert (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper presents the experiences of advisers in implementing the concept of CSR in Polish enterprises. The article presents the results of surveys covering such issues as the implementation of CSR motives and actions taken by operators in the implementation of CSR policies. CSR advisors also identified that companies can use unethical practices. This is also a characteristic of CSR advisors.